2021
DOI: 10.1590/s1678-9946202163050
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 reinfection: report of two cases in Southeast Brazil

Abstract: From February 26, 2020 to March 11, 2021, coronavirus disease 2019 (COVID-19) pandemic resulted in 11,439,558 cases and 277,102 deaths in Brazil. Among them, 2,195,130 cases and 63,965 deaths occurred in Sao Paulo State, Southeast Brazil. The recent emergence and rise of new variants of SARS-CoV-2 is of concern because of their higher transmissibility and possible association with more severe disease. Cases of SARS-CoV-2 reinfections have been described since December 2020 in Brazil. This report describes two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…So far, reinfections are rare as some studies show primary infections to generate a protective immune response in most cases ( 56 59 ). Nonetheless, various case reports describe reinfections often being associated with low immune responses during the first infection as well as different strains of SARS-CoV-2 infecting one individual ( 60 63 ). Although the individual in the present study presented clear signs of a specific immune response after the first infection, immune cells, antibody levels and SARS-CoV-2-specific T cells decreased within 32 weeks post symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…So far, reinfections are rare as some studies show primary infections to generate a protective immune response in most cases ( 56 59 ). Nonetheless, various case reports describe reinfections often being associated with low immune responses during the first infection as well as different strains of SARS-CoV-2 infecting one individual ( 60 63 ). Although the individual in the present study presented clear signs of a specific immune response after the first infection, immune cells, antibody levels and SARS-CoV-2-specific T cells decreased within 32 weeks post symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…Two case reports reported on patients who had been vaccinated before reinfection. One patient developed reinfection 10 days after the first dose bur did not report the vaccine type [68]. Another patient developed reinfection 13 days after the first dose of Pfizer vaccination was administered [41].…”
Section: Vaccinationmentioning
confidence: 99%
“…In the included studies, viral gene sequencing revealed mutations among some patients. Of the 29 studies that reported mutations in details, D614G was the most common mutation [10, 34-36, 38, 39, 42, 47-49, 52, 60, 62, 64, 65, 67, 68, 70, 71], and other mutations such as N440K [70] and E484K [50,68,69] were also detected. See Additional file 1: Table S7.…”
Section: Viral Mutations Of Reinfected Casesmentioning
confidence: 99%
“…Cases of reinfection have been reported since the beginning of the pandemic (12,20,(52)(53)(54), including in Brazil (55)(56)(57). Studies have shown that an acquired immune response can reduce the risk of transmission by up to 90%, with an interval of 6-10 months (58)(59)(60).…”
Section: Discussionmentioning
confidence: 99%